\(đk:x\ne0;x\ne-7\\ c,\dfrac{7x+6}{2\left(x+7\right)}-\dfrac{3x+6}{2x^2+14x}\\ =\dfrac{7x+6}{2\left(x+7\right)}-\dfrac{3x+6}{2x\left(x+7\right)}\\ =\dfrac{x\left(7x+6\right)-\left(3x+6\right)}{2x\left(x+7\right)}\\ =\dfrac{7x^2+6x-3x-6}{2x\left(x+7\right)}\\ =\dfrac{7x^2+3x-6}{2x\left(x+7\right)}\)
\(c,\dfrac{7x+6}{2x\left(x+7\right)}-\dfrac{3x+6}{2x^2+14x}\\ =\dfrac{7x+6}{2x\left(x+7\right)}-\dfrac{3x+6}{2x\left(x+7\right)}\\ =\dfrac{7x+6-3x-6}{2x\left(x+7\right)}\\ =\dfrac{4x}{2x\left(x+7\right)}\\ =\dfrac{2}{x+7}\)
\(\dfrac{7x+6}{2x^2+14x}=\dfrac{3x+6}{2x\left(x+7\right)}\)
\(\dfrac{7x+6}{2x\left(x+7\right)}-\dfrac{3x+6}{2x\left(x+7\right)}\)
\(=\dfrac{\left(7x+6\right)-\left(3x+6\right)}{2x\left(x+7\right)}\)
\(=\dfrac{7x+6-3x-6}{2x\left(x+7\right)}=\dfrac{4x}{2x\left(x+7\right)}=\dfrac{2}{x+7}\)